Questionnaire-Driven: Konfigurasi Sistem Informasi Pembayaran SPP Sekolah - Faizin, Muhammad Syahrul; Abidin, Muhammad Fahmi; Usman, Baso Abrar; Yaqin, M. Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Schools must have a process model which describes the structured flow that is appropriate in every action to be taken in activities at the school, especially in payment process SPP. Even though it has entered the millennial era, there are still many schools that use the SPP payment process model using the manual method, because they have to adjust to the environment. To get the appropriate process model, an information system configuration is needed in which an information system can create an appropriate process model. To configure an information system, it must obtain configuration data from the environment obtained through Questionnaire-Driven. From the data obtained from Questionnaire-Driven, an information system configuration process is carried out to determine the payment process model of the school SPP payment system.